Theoretical Chemistry Accounts Theory, Computation, and Modeling - Truhlar, Donald G.; Adamo, Carlo; Ciofini, Ilaria; Yang, Weitao; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
TCA publishes papers in all fields of theoretical chemistry, computational chemistry, and modeling. Fundamental studies as well as applications are included in the scope. In many cases, theorists and computational chemists have special concerns which reach either across the vertical borders of the special disciplines in chemistry or else across the horizontal borders of structure, spectra, synthesis, and dynamics. TCA is especially interested in papers that impact upon multiple chemical disciplines. TCA was founded in 1962 specifically to provide theoretical chemists with a high-quality, peer reviewed communication medium for their work. The TCA Letters section guarantees review of manuscripts submitted for the Letters section within four weeks of their receipt to meet the need for rapid publication. In response to the need for accounts that assist researchers in maintaining a perspective on important recent developments, TCA also publishes overviews, either of a coherent body of work or of an especially rapidly developing subfield of theoretical or computational chemistry. Finally, TCA publishes regular articles reporting original work. Such articles contain full details of the theory and/or computations. TCA encourages authors to take advantage of the opportunities offered by electronic publishing and maintains an internet archive for the viewing, storage, and downloading of supplementary material for papers published in TCA.
Keywords: Inorganic chemistry; Organic chemistry; Physical chemistry; Chemistry, Physical and theoretical; Atomic structure; Molecular structure; Spectra; Theoretical and Computational Chemistry; Inorganic Chemistry; Organic Chemistry; Physical Chemistry; Atomic/Molecular Structure and Spectra